MENA Quarterly Economic Brief, July 2016 : Whither Oil Prices? - Devarajan, Shantayanan; Mottaghi, Lili (Washington, DC: World Bank, 2016)
This issue of the World Bank MENA Quarterly Economic Brief seeks to understand the factors behind the new normal of the oil market to discern the evolution of world oil prices in the future, and their implications for the economies of the Middle East and North Africa (MENA). Our findings show that the oil price crash of 2014 was preceded by a significant increase in the size and frequency of volatility of oil prices. This volatility in turn contributed to the accumulation of oil inventories, attributing to the decline in oil prices. Noting that, historically, oil price slumps have lasted longer than spikes, we suggest that the current situation in the oil market may persist because of the changing behavior of market players, and the fact that overall oil demand is weak and not expected to rebound anytime soon. We expect the world oil market to work through its current oversupply and rebalance in early 2020 at market-clearing prices that are close to the marginal cost of the last producer (US shale oil producers). Oil prices are likely to be in the range of $53 - $60 a barrel and stay there for several years. The new normal for oil prices will prove difficult for MENA oil producers and could end up overhauling the existing social contract.